Consideration of runouts by the evaluation of fatigue experiments - Toasa Caiza, Paul Dario (Berichte zum Stahl- und Leichtbau / Karlsruher Institut für Technologie, Versuchsanstalt für Stahl, Holz und Steine, Stahl- und Leichtbau, 2019)
In EC3, the fatigue life of a steel structure subjected to a cyclic load is estimated by its detail category. This category is based on the S-N, curves which are obtained by applying the Basquin model. Statistically, this model does not allow extrapolating the S-N curves in the HCF region, neither does it consider the runouts. This affects the fatigue life estimation when a structure bears loading in HCF. To overcome these deficiencies, a new method based on a Weibull distribution is applied.